Professional practices in the health area: challenges and consequences in the framework of the Covid-19 pandemic (Emancipação, 2021)
This document corresponds to a state of the art in which the challenges faced by professionals working in the health area are examined, in the framework of the pandemic generated by the Covid-19. A bibliographic search was carried out in the following databases: Scielo, Redalyc, Dialnetand Google Scholar, finding a final sample of 40 articles. From the reading and analysis of the publications made on the subject, 3 categories of analysis are deduced: 1) Public Health Policy and Covid-19; 2) Working conditions and effects on the health of professionals; and 3) effect on the mental health of professionals. The results of this systematic review show that the challengesfaced affect health professionals with serious consequences, both physical, mental and social.
Keywords: Professionals and public policies. Public policies and pandemic. Health professionals and Covid.; Mental health and covid-19.